Uncertainty Entangled; Modelling Safety Assurance Cases for Autonomous Systems - Mjeda, Anila; Botterweck, Götz (Electronic Communications of the EASST, 2021)
When designing and analysing autonomous systems and their environment it is necessary to consider uncertainty and multiple potential states (of the system and its environment). In this position paper, we explore the idea of notations and modelling tools that are based on ‘superpositions’ of states. More concretely, we present a treatment of uncertainty in autonomous systems inspired by quantum physics and propose an extension of the Goal Structuring Notation (GSN), a common approach for the modelling of safety arguments, to model ’superposition’ and ’entangled’ nodes; and, incorporate guidelines of the emerging UL 4600 standard for autonomous systems.